Pengembangan E- Modul Berbasis Technopreneurship Pada Proses Pembelajaran Instalasi Listrik Industri - Nadira Zulnia Putri; Elfizon Elfizon (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
The purpose of this research is to develop a valid, practical, and effective technopreneur-based e-module to increase the entrepreneurial spirit in the industrial electrical installation course majoring in Electrical Engineering, Faculty of Engineering, State University of Padang. This type of research is R & D, this research uses a 4D model research procedure, which consists of four stages, namely define, design, develop, and disseminate. The research subjects are D4 Electrical Engineering students, Faculty of Engineering, State University of Padang. The validation test consists of three validators consisting of two material expert validators and one media expert validator. The practicality test was carried out by two lecturers of the industrial electrical installation course and ten students from the D4 Electrical Engineering study program, Faculty of Engineering, the State University of Padang as respondents for the development of learning e-modules. Effectiveness data were obtained from the use of posttest to evaluate student learning outcomes. Based on the results of the research that has been done, it can be seen that the development of this e-module has succeeded in producing valid, practical, and effective media. The results of the validity test of the three validators were categorized as very valid. The results of the practicality test by the subject lecturers are categorized as very practical, while the results of the practicality tests by students are categorized as very practical. The results of the effectiveness test obtained that classical completeness meets the category so that it can be said to be very effective. Thus, the e-learning module based on technopreneurship as a learning medium is effectively used in the lecture process in the Department of Electrical Engineering, Faculty of Engineering, State University of Padang.